Size and Shape Effect on Melting Temperature of Metallic Nanocrystals - Liqin ZHANG; Shitao XU (Medžiagotyra, 2025)
The melting temperature serves as a pivotal physical property governing the thermal stability of metallic nanocrystals, notably exhibiting substantial variability with respect to size and dimensionality. While several quantitative models exist to elucidate how the melting temperature correlates with the size and dimensionality of metallic nanocrystals, these models often fall short of capturing the synergistic influence of both factors comprehensively. To address this gap, our study employs a novel thermodynamic framework grounded in cohesive energy theory, requiring no arbitrary adjustable parameters. We find that, under constant conditions, the melting temperature of metallic nanocrystals diminishes as their size decreases. In terms of dimensionality, we establish a hierarchy as follows: nanoparticles > nanowires > thin films. Moreover, we reveal a non-linear relationship between the melting temperature and the inverse of dimensionality. Through rigorous validation via both simulations and empirical experiments, we corroborate the high accuracy of this thermodynamic model in predicting the variations in the melting temperature of metallic nanocrystals due to changes in size and dimensionality. The model in this study is primarily applicable to metallic nanocrystals and the potential applicability to other types of nanocrystals under certain conditions is briefly mentioned..